Linking changes in species composition and biomass in a globally distributed grassland experiment. (24th October 2022) - Ladouceur, Emma; Blowes, Shane A.; Chase, Jonathan M.; Clark, Adam T.; Garbowski, Magda; Alberti, Juan; Arnillas, Carlos Alberto; Bakker, Jonathan D.; Barrio, Isabel C.; Bharath, Siddharth; Borer, Elizabeth T.; Brudvig, Lars A.; et al.
Abstract: Global change drivers, such as anthropogenic nutrient inputs, are increasing globally. Nutrient deposition simultaneously alters plant biodiversity, species composition and ecosystem processes like aboveground biomass production. These changes are underpinned by species extinction, colonisation and shifting relative abundance. Here, we use the Price equation to quantify and link the contributions of species that are lost, gained or that persist to change in aboveground biomass in 59 experimental grassland sites. Under ambient (control) conditions, compositional and biomass turnover was high, and losses (i.e. local extinctions) were balanced by gains (i.e. colonisation). Under fertilisation, the decline in species richness resulted from increased species loss and decreases in species gained. Biomass increase under fertilisation resulted mostly from species that persist and to a lesser extent from species gained. Drivers of ecological change can interact relatively independently with diversity, composition and ecosystem processes and functions such as aboveground biomass due to the individual contributions of species lost, gained or persisting. Abstract : We link changes in species composition to changes in biomass through time in a globally distributed grassland experiment. We investigate how local extinctions, colonisations and species that persist contribute to biomass change under fertilization (NPK) and under ambient conditions (control) through time. We show that the relationship between compositional and biomass changes depends on the component contributions of species that leave, enter or persist in communities experiencing global change.